A new convenient synthetic approach to diarylpyrimidines. Issue 27 (7th July 2016) - Guirado, Antonio; Alarcón, Enrique; Vicente, Yesica; Andreu, Raquel; Bautista, Delia; Gálvez, Jesús
Abstract: A new synthetic method in pyrimidine chemistry has been developed. 2, 2, 2-Trichloroethylideneacetophenones, easily available from chloral and acetophenones, reacted with benzamidines to provide novel 2, 6-diaryl-6-hydroxy-4-trichloromethyl-1, 4, 5, 6-tetrahydropyrimidines in near quantitative yields. Efficient dehydration of these compounds gave previously unknown 2, 4-diaryl-6-trichloromethyl-1, 6-dihydropyrimidines, which were found able to undergo base-induced chloroform elimination to give 2, 4-diarylpyrimidines in high yields. Molecular structures for final and intermediate compounds were determined by single crystal X-ray diffraction. A main improvement of this procedure lies in circumventing the oxidative aromatization of dihydropyrimidine intermediates through a chloroform elimination process. The diarylpyrimidines were also found directly accessible by a fair yield one-pot procedure. Graphical abstract: